Clustering and Principal Component Analyses of Constraints in Smallholding Pig Keeping Systems in Manokwari, Indonesia - Iyai, DA; Woran, D; Sumpe, I (ANIMAL PRODUCTION, 2010)
The research was aimed at identifying clusters and constraints on small holding pig keeping systems in Manokwari, Papua.  A total of 50 pig farmers were selected purposively from 15 villages in urban and rural areas of Manokwari. Questions were focused on the constraints of small holding pig keeping systems development in Manokwari. To classify constraints, a total of seven constraints have been noted.  Agglomerative hierarchical clustering (AHC) and principle component analysis (PCA) were used for clustering analysis and grouping based on components of constrains. Feeding and breeding had Eigen values of 9487 and 2010, respectively. Furthermore, Feeding and breeding had higher variability compared with other components that were 63.250 and 13.397%, respectively (Cumulative axis 1 and 2 were 76.65%). Feeding and breeding had a positive coefficient correlation (Pearson n) rF1 that could be found in some farmers in urban and rural of Manokwari. (Animal Production 12(3): 199-206 (2010) Key Words: pig, small holding systems, clustering, component analysis, development constraints, Papua